PEDAGOGICAL ESSENCE OF THE COMPETENCY-BASED APPROACH AND ITS ROLE IN MUSIC EDUCATION - Omonova Fayziniso Anvar qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the pedagogical essence of the competency-based approach, its didactic potential in music education, and its role in learning outcomes assessment (competency-based assessment). The research design employs comparative analysis of regulatory and legal documents (Uzbekistan’s State Educational Standards and higher education standards), scholarly literature, and international experience. The results show that the competency-based approach in music education strengthens an outcome-oriented model focused not merely on “knowledge,” but on performance- based activity, creative products, reflection, and digital pedagogy. Teacher competencies are shown to be systematically developed through TPACK and digital competence frameworks. Although the competency-based paradigm is being consolidated in Uzbekistan through state educational standards, several “gaps” remain in music education, particularly in assessment criteria, integration of digital competence, and methodological support for teachers. Based on international experience, the discussion proposes a “music education competency matrix” adapted to the Uzbek context, along with a rubric-based assessment model.